2020
DOI: 10.4103/jfmpc.jfmpc_805_20
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone use and the quality of life of medical students in the Kumaun Region, Uttarakhand

Abstract: Background: Once a device for telecommunication, now a powerful device bringing the whole world in one's palm, smartphones are increasingly becoming a common commodity among the medical students. Smartphones foster social interaction and facilitate multitasking and learning, but they also have some adverse effects. Young people, especially students, who are always inquisitive towards new technology, are likely to be affected by both these positive and negative impacts. Objective: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…[13][14][15] Earlier studies reported that in south India, the prevalence of smartphone addiction is less. 16 However, in our study, we have observed a higher prevalence of over usage of smartphones by medical students. Interestingly, it was reported that female students use more time than males.…”
Section: Discussioncontrasting
confidence: 61%
“…[13][14][15] Earlier studies reported that in south India, the prevalence of smartphone addiction is less. 16 However, in our study, we have observed a higher prevalence of over usage of smartphones by medical students. Interestingly, it was reported that female students use more time than males.…”
Section: Discussioncontrasting
confidence: 61%
“…A study (Beck et al, 1988) The mentioned differences between some of the previous studies and those of the present research can be attributed to the differences in the questionnaires measuring smartphone addiction. In the present study, MPAS was used to measure mobile phone addiction, but the Smartphone Addiction Scale designed by Kwon et al was employed in most of the studies mentioned above (Kwon et al, 2013a;Chen et al, 2017;Alhazmi et al, 2018;Awasthi et al, 2020). Moreover, in the Persian version of MPAS, whose reliability and validity were examined by Mazaheri et al (Mazaheri and Karbasi, 2014), scores below 30 were classified as lack Based on Chi-square test.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, MPAS was used to measure mobile phone addiction, but the Smartphone Addiction Scale designed by Kwon et al . was employed in most of the studies mentioned above (Kwon et al ., 2013a; Chen et al ., 2017; Alhazmi et al ., 2018; Awasthi et al ., 2020). Moreover, in the Persian version of MPAS, whose reliability and validity were examined by Mazaheri et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are potentiating the findings of a cross-sectional study conducted among the undergraduate medical students of GMC Haldwani, which showed that smartphone addiction is high among medical students and has a significant negative impact on their QOL (quality of life). [ 26 ] For depression, 56.6% of participants showed no depressive symptoms, while 15.6% had symptoms for mild depression, 16% for moderate depression, and 11.6% for severe and extremely severe depression, which is alarming as nearly 43.3% of participants showed depressive symptoms. The reason for above above-noted prevalence can be multifactorial.…”
Section: Discussionmentioning
confidence: 99%